Childhoods, sexualities and the school in times of neoconservatism and post-fascism - Acosta, Tássio [UNESP]; Gallo, Sílvio (Universidade de Estado do Rio de Janeiro, 2024)
This paper seeks to analyze various developments in the relationship between childhoods, youth and sexualities that have appeared in public schools in the era of restriction and persecution that has characterized sex education over the course of the last decade in Brazil. To speak about childhood is to speak about bodies and as such, to speak about sexuality, and the interpersonal relationships that occur in school spaces, which are primary, essential sites of sex and gender socialization. As such, in the face of the censorship imposed on these themes in recent educational plans and policies, as well as in the National Common Curricular Base, and in the face of the systematic persecution of teachers interested in exploring these issues, our intention in this paper is to investigate the place of the body and sexuality in school settings, especially in times of neoconservatism and post-fascism. By the former, we understand those new agencies that promote and propagandize a set of reactionary values among the Brazilian population; by the latter, we mean those spheres of sociability and collective action and reaction that function in an atmosphere of moral panic, and promote an ideology saturated by both implicit and explicit violence and repression. To support our analysis, we explore three school settings whose practice of sexuality education acts to resist neoconservative and post-fascist norms. These three cases, vilified as they are in the right wing mainstream as being responsible for the destruction of the traditional heteronormative Brazilian family, should, we argue, be valued as educational practices that promote safe childhoods and positive social reconstruction.
Infâncias, Juventudes E Sexualidades Na Escola Em Tempos De Neoconservadorismo E Pós-Fascismo
Keywords: childhoods; neoconservatism; post-fascism; sexualities